Isotopic calcium biogeochemistry of MIS 5 fossil vertebrate bones: application to the study of the dietary reconstruction of Regourdou 1 Neandertal fossil. Issue 151 (February 2021) - Dodat, Pierre-Jean; Tacail, Théo; Albalat, Emmanuelle; Gómez-Olivencia, Asier; Couture-Veschambre, Christine; Holliday, Trenton; Madelaine, Stéphane; Martin, Jeremy E.; Rmoutilova, Rebeka; Maureille, Bruno; Balter, Vincent
Abstract: The calcium isotopic composition (δ 44/42 Ca) of bone and tooth enamel can be used for dietary reconstructions of extant and extinct mammals. In natural conditions, the δ 44/42 Ca value of bone and teeth varies according to dietary intake with a constant isotopic offset of about −0.6‰. Owing to the poor conservation of collagen, carbon (C), and nitrogen (N) isotopic compositions of the Regourdou Mousterian site (MIS 5, Dordogne, France) previously failed to provide any paleodietary information. Therefore, to reconstruct the trophic chain, we have measured calcium (Ca) isotopes from fossil bone samples of the fauna from the Regourdou site, as well as from three bone samples of the Regourdou 1 Neandertal specimen. The results show a taxon-dependent patterning of the Ca isotopic compositions: herbivores generally have higher δ 44/42 Ca values than carnivores. All the δ 44/42 Ca values of Regourdou 1 are low (<-1.6‰), placing this specimen amid carnivores. Using a bone-muscle Ca isotopic offset determined on extant animals, we further show that the δ 44/42 Ca value of the Regourdou 1 diet, and that of most carnivores, cannot be accounted for by the consumption of meat only, as plants and meat have indistinguishable δ 44/42 Ca values. Mass balance calculations indicate that the low δ 44/42 Ca values of the Neandertal's carnivorous diet are explained by the ingestion of bone marrow containing as little as 1% trabecular bone. Our results show that the Regourdou 1 Neanderthal consumed a mixture of various herbivorous prey, as well as trabecular bone, which probably occurred when marrow was ingested, by accident or intentionally.